URGENSI MEMAHAMI PSIKOLOGI ANAK DALAM PROSES PEMBELAJARAN - Choiri, Moh. Miftahul; Festian Cindarbumi; Auliyaur Rokhim (Discovery, 2025)
The success or failure of a learning process is determined by the teacher. Teachers need to understand educational psychology so that learning can be achieved optimally. Teachers need to understand how each student learns. By understanding how each student learns, you will be able to provide appropriate treatments in learning. In this way the learning process will be successful. For example, there are students who like to learn with visual media or there are also those who use audio-visual and even apply kinesthetic learning methods and so on. All the different ways of learning must all be facilitated by the teacher. The research method in this research is Library Research, namely collecting library sources that are relevant to theoretical studies. Relevant theories are analyzed and synthesized so that in the end they can be used as references by readers. This research aims to serve as a reference for teachers and learners so that they can carry out the teaching process well, optimally and achieve the expected learning objectives. Keywords: Urgency, Psychological Approach, Learning Process